Epigenetics: A link between toxicants and diseases - Anna Romanò; Christina Pagiatakis; Rosalba Gornati; Giovanni Bernardini; Roberto Papait (iScience)
Summary: Epigenetics is a complex network of molecular mechanisms, including DNA modifications, histone modifications, and non-coding RNA transcripts that influence gene transcription in heritable ways across cells. Over the last decades, epigenetic mechanisms have gained significant attention in the field of toxicology. Various research groups are investigating the epigenetic impact of toxicants due to their role in mediating the effects of environmental factors on cellular function, in complex diseases, and in explaining adverse effects on offspring. Here, we give an overview of these studies, exploring the intersection of epigenetics and toxicology and focusing on how not only environmental pollutants but also recreational substances, such as tobacco smoke and alcoholic beverages, can impact DNA and histone modifications.